2010
DOI: 10.1097/bot.0b013e3181f6c001
|View full text |Cite
|
Sign up to set email alerts
|

Suprapatellar versus Infra-Patellar Intramedullary Nail Insertion of the Tibia: A Cadaveric Model for Comparison of Patellofemoral Contact Pressures and Forces

Abstract: It is known that structural integrity of articular cartilage is compromised at impact loads exceeding 25 MPa, and chondrocyte apoptosis can occur at sustained loads of as little as 4.5 MPa in immature bovine cartilage. The results of this study indicate that although the patellofemoral contact pressures are higher with SP nail insertion, they remain below the values reported to be detrimental to articular cartilage. Based on these data, we do not believe that the SP entry portal poses a significant risk to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 11 publications
1
72
0
Order By: Relevance
“…[10][11][12] To our knowledge, this is the first report of a randomized clinical trial comparing IP and SP tibial IMN approaches. Although this was only a pilot study, our results show that the SP approach is equivalent to the traditional IP technique with regard to union, alignment, knee pain, and functional outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…[10][11][12] To our knowledge, this is the first report of a randomized clinical trial comparing IP and SP tibial IMN approaches. Although this was only a pilot study, our results show that the SP approach is equivalent to the traditional IP technique with regard to union, alignment, knee pain, and functional outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…showed in human cadaver specimens that despite increased intraarticular pressure during the suprapatellar approach the maximum pressure stayed well below the pressure at which apoptosis of chondrocytes occur. 6 Furthermore Courtney et al postulated in the first retrospective cohort study of functional knee scores associated with traditional infrapatellary nailing and suprapatellar nailing that the suprapatellar entry portal is a safe alternative for tibia nailing with use of appropriate instrumentation. 7 Traditional technique for the intramedullary nailing of the tibia requires that the knee be resting in a flexed or fully flexed position.…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted studies of articular damage, both in the laboratory and clinical settings. Gelbke et al 25 showed in a cadaver biomechanical study that the forces engendered in transarticular suprapatellar nailing exceeded the forces in the patellofemoral joint with infrapatellar tibial nailing. The forces measured remained below the reported threshold for chondrocyte death and below the contact pressures measured with simple knee flexion.…”
Section: Suprapatellar Nailingmentioning
confidence: 99%